Całkowicie prywatna opieka medyczna — próba zarysu - Wójtowicz, Stanisław; Rozynek, Kamil (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
In this paper, we explore what the market for medical services and products could look like if the state completely withdrew from the area of medical care. In section 1, we demonstrate that medical services would be purchased mainly through direct payments and medical insurance. We analyse two models of medical insurance: guaranteed renewable insurance and health-status insurance. Other types of insurance that may emerge on the market are also discussed. In section 2, we examine how the privatisation of the health-care system would affect the prices of medical services. We analyse fundamental problems of the state-run health care and discuss how they contribute to smaller supply and higher prices of medical services. We then describe how the introduction of market mechanisms would allow to solve many of these problems. We argue that internalisation of the costs of medical care in a free market order would create strong economic incentives for individuals to take better care of their health, and we contrast this with the state-run health care in which these costs are externalised. In section 3, we explore how medical services could be obtained by individuals without sufficient funds. In section 4, we discuss how the quality of medical care could be ensured without the help of the state. We argue that competition between service providers would be the main guarantor of quality. We also identify mechanisms that would lead to spontaneous emergence of a system of private medical licencing.
Keywords: health care; private health care insurance; health behaviour